Circular RNA cMTO1 Promotes PTEN Expression Through Sponging miR-181b-5p in Liver Fibrosis - Jin, Hui; Li, Chunxue; Dong, Peihong; Huang, Junting; Yu, Jinglu; Zheng, Jianjian (Frontiers in Cell and Developmental Biology, 2020)
Background: Circular RNAs (circRNAs) are considered as key regulators of cancer biology. Recently, cMTO1 (a circRNA derived from MTO1 gene, hsa_circ_0007874) has been demonstrated to act as a tumor suppressor in hepatocellular carcinoma. However, the roles of cMTO1 in liver fibrosis are largely unknown. Methods: Expressions and roles of cMTO1 were examined in vivo and in vitro during liver fibrosis. The interaction between microRNA-181b-5p (miR-181b-5p) and cMTO1 was analyzed by luciferase activity assays and pull down assays. Results: cMTO1 was shown to be reduced in the liver from patients with cirrhosis. In addition, cMTO1 was down-regulated in the mouse fibrotic livers as well as activated hepatic stellate cells (HSCs). Restoring of cMTO1 led to a reduction in HSC proliferation. Results of immunofluorescence analysis showed that cMTO1 suppressed the expressions of α-SMA and type I collagen. cMTO1 was found to be expressed in the cytoplasm of HSCs. Further studies confirmed that cMTO1 and miR-181b-5p were co-located in the cytoplasm. Interestingly, there was an interaction between cMTO1 and miR-181b-5p. Results of luciferase reporter assays and pull down assays confirmed that miR-181b-5p could bind to cMTO1. cMTO1-inhibited HSC activation was blocked down by miR-181b-5p or PTEN. Meanwhile, PTEN was a target of miR-181b-5p. Conclusion: cMTO1 inhibits HSC activation, at least in part, through miR-181b-5p-mediated PTEN expression. Our results also suggest that cMTO1 may be a novel therapeutic target in liver fibrosis.